Cold Oxidative Demetalation of Aryl Organometallics: A Novel Route to Demetalate Ullmann Intermediates without Heating. Issue 10 (7th March 2023) - Pérez Paz, Alejandro
Abstract: A new way of demetalating Ullmann organometallic aryl intermediates is proposed that uses charging rather than heating conditions. Ab initio molecular dynamics simulations show that certain aryl organosilver and organocopper intermediates (MPh2, with M=Cu, Ag and Ph=phenyl group) spontaneously demetalate even starting with zero velocities upon the oxidative removal of one electron. The oxidative demetalation is driven by the loss of electron density in the interatomic C−M region and leads to a biphenyl molecule with a η ‐coordinated nearby M atom. The main advantage of this dry redox demetalation process is that it avoids the use of high temperatures which have deleterious effects on the yields. The method does not compromise the thermal stability of the end product and reduces the chances of uncontrolled side reactions. The demetalation of oxidized MPh2 is predicted to occur spontaneously in the gas phase and on an inert surface. A possible experimental setup is proposed to test this idea in the widely‐used Ullmann reaction for the controlled on‐surface synthesis of new C−C bonds. The reduction‐induced planarization of the neutral MPh2 molecule is reversible and could be used as an electro‐mechanical nano‐switch. The neutral and anionic compounds are predicted to be locally aromatic and dynamically stable. For bimetallic aryl intermediates (M2 Ph3 ), the irreversible demetalation occurs upon the removal of two electrons leading to the dication. Abstract : Computer simulations show the spontaneous oxidative demetalation of suitable aryl organocopper and organosilver compounds at ultralow temperatures. This finding could be used as an alternative way to demetalate stable Ullmann organometallic intermediates without the need of thermal annealing.